Novel Immunotherapies for Osteosarcoma - Lu, Yubao; Zhang, Jiahe; Chen, Yutong; Kang, Yuchen; Liao, Zhipeng; He, Yuanqi; Zhang, Cangyu (Frontiers in Oncology, 2022)
Osteosarcoma (OS) is the most common primary malignant bone sarcoma mainly affecting adolescents and young adults, which often progresses to pulmonary metastasis and leads to the major cause of death of OS patients. OS is characterized as a highly heterogeneous cancer type and the underlying pathologic mechanisms triggering tumor progress and metastasis are incompletely recognized. Surgery combined with neoadjuvant and postoperative chemotherapy has elevated 5 year survival over 70% for patients with localized OS tumor, as opposed to only 20% patients with recurrence and/or metastasis. Therefore, novel therapeutic strategies are needed to overcome the defeats of conventional treatments. Immunotherapy is gaining momentum for the treatment of OS with increasing number of FDA-approved therapies for malignancies resistant to conventional therapies. Here, we review the OS tumor microenvironment and appraised promising immunotherapies available in the management of OS.